2008
DOI: 10.1080/13697130802416640
|View full text |Cite
|
Sign up to set email alerts
|

Androgens in relationship to cardiovascular risk factors in the menopausal transition

Abstract: An increment in the androgenic milieu that correlates with abdominal fat, insulin resistance and atherogenic lipoproteins becomes evident after the menopausal transition and suggests that evaluation of cardiovascular disease risk in these women should include androgens, considering that abdominal obesity is one of the main determinants of the relationship between androgenic parameters and cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 35 publications
(25 reference statements)
1
21
1
1
Order By: Relevance
“…Our studies also showed that, as the menopausal transition goes ahead, androgenic status increases in association with abdominal fat deposition [9]. It should be remarked that waist circumference is an interesting surrogate marker of abdominal obesity, and we observed that abdominal obesity, more than menopausal status, is the main determinant of the differences found in androgenic profile.…”
supporting
confidence: 78%
“…Our studies also showed that, as the menopausal transition goes ahead, androgenic status increases in association with abdominal fat deposition [9]. It should be remarked that waist circumference is an interesting surrogate marker of abdominal obesity, and we observed that abdominal obesity, more than menopausal status, is the main determinant of the differences found in androgenic profile.…”
supporting
confidence: 78%
“…Studies have already shown that elevated androgens and low SHBG are related to metabolic variables associated with CVD risk (11)(12)(13). However, some studies have shown that upon controlling for VAT, the relationship between metabolic variables and SHBG and/or bioavailable testosterone is no longer found (14)(15)(16). Furthermore, others have postulated that it is the bioavailable testosterone that regulates VAT accumulation associated with CVD risk, and may even directly contribute to CVD risk (10,17).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study, our group evaluated the relationship between androgens and cardiovascular risk factors in the menopausal transition [15]. We found an increment in the androgenic milieu that correlated with abdominal fat, insulin-resistance, and atherogenic lipoproteins.…”
Section: Androgens/testosteronementioning
confidence: 99%
“…Concerning estradiol levels in this period of life, they are frequently higher than those found in premenopausal women [13,14], but, indeed, estradiol concentrations in perimenopausal women show a high degree of variability [13]. In turn, changes in androgen levels during the menopausal transition are controversial, although it is generally accepted that testosterone levels do not change significantly in this period of life [15]. Given that alterations of the hormonal profile begin in the early 40s, in the menopausal transition, consequently, changes in risk factors for CVD (such as anthropometric characteristics) could also be observed in this period.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation